Strategi Perekrutan dan Pelatihan dalam Mengurangi Angka Pengangguran pada Dinas Tenaga Kerja dan Transmigrasi Kabupaten Karawang - Abdul Anhar Hidayat; Wanta; Dwi Epty Hidayaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In Karawang Regency, the high open unemployment rate in 2020 reached 11.52%, becoming a serious challenge that has the potential to cause negative impacts such as poverty, increased crime, school dropouts, and an increase in the number of beggars on the streets. This research aims to find effective strategies in reducing the unemployment rate in Karawang Regency through recruitment and training policies. This research uses qualitative research methods, located at the Karawang Regency Manpower and Transmigration Service. In this research, the data analysis technique used is a qualitative technique. Data source testing is carried out through the triangulation method, which aims to ensure that information from different sources is re-evaluated. Apart from that, expansion can be done by combining the results of the interviews. Strategies for reducing the unemployment rate in Karawang Regency include recruitment through the infoloker website which focuses on local placements and competency-based training to improve job seeker skills. As a result, the Karawang Manpower Office has succeeded in implementing an effective strategy in reducing unemployment in Karawang Regency. This strategy includes competency-based training and recruitment via the infoloker website. Competency-based training ensures trainees develop skills and knowledge that are relevant and applicable in their work context. Meanwhile, the infoloker website facilitates the job search process, making it more effective and efficient for labor users and job seekers. These strategies have shown a positive impact in reducing unemployment and improving the quality of the workforce in Karawang Regency.